2006
DOI: 10.1001/archotol.132.10.1053
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Elevated EphB4 Expression, Smoking Status, and Advanced-Stage Disease in Patients With Head and Neck Squamous Cell Carcinoma

Abstract: To examine the expression of EphB4 in tumor tissue, surrounding normal tissue, and metastatic lymph node in patients with head and neck squamous cell carcinoma (HNSCC) and to evaluate its association with disease stage and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…The expression trend described here for HNSCC is in close agreement with reports by Masood et al (Masood et al, 2006), which found that tumor expression of EPHB4 in HNSCC increased with disease stage (in primary tumor tissues and nodal metastases), by Sinha et al (Sinha et al, 2006), which reported that EPHB4 expression correlated both with stage of HNSCC as well as with progression from normal status to cancer, and by Yavrouian et al (Yavrouian et al, 2008), which demonstrated that increased EPHB4 expression in HNSCC is correlated with shorter survival. However, no previous studies have investigated the expression of EPHB4 in pre-HNSCC dysplastic tissue; to our knowledge, these data are the first to address the expression pattern of a kinase in paired head and neck tissues with progression from normal status through dysplasia to cancer and therefore shed significant light on the role of EPHB4 in HNSCC progression.…”
Section: Discussionsupporting
confidence: 93%
“…The expression trend described here for HNSCC is in close agreement with reports by Masood et al (Masood et al, 2006), which found that tumor expression of EPHB4 in HNSCC increased with disease stage (in primary tumor tissues and nodal metastases), by Sinha et al (Sinha et al, 2006), which reported that EPHB4 expression correlated both with stage of HNSCC as well as with progression from normal status to cancer, and by Yavrouian et al (Yavrouian et al, 2008), which demonstrated that increased EPHB4 expression in HNSCC is correlated with shorter survival. However, no previous studies have investigated the expression of EPHB4 in pre-HNSCC dysplastic tissue; to our knowledge, these data are the first to address the expression pattern of a kinase in paired head and neck tissues with progression from normal status through dysplasia to cancer and therefore shed significant light on the role of EPHB4 in HNSCC progression.…”
Section: Discussionsupporting
confidence: 93%
“…EphB4 is similarly over-expressed in head and neck cancers (100% of 37 cases examined) and knockout studies using siRNA and antisense both in vitro and importantly, in vivo , have demonstrated that EphB4 has an essential role in many processes that contribute to cancer cell survival and spread [16,17]. Cytokeratins such as CK19 are almost exclusively expressed in epithelial tissues and are commonly used as markers for the detection of disseminated tumour cells of epithelial origin [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, EphB4 expression is limited in normal adult tissue12, which makes it an ideal target for therapeutic intervention. Previous studies have reported an association between EphB4 overexpression and advancement of disease13. Winter et al .…”
mentioning
confidence: 97%